High-temperature reduction thermochemistry of SrVO3−δ - Krishna K Ghose; Yun Liu; Terry J Frankcombe (JPhys Energy, 2023)
Cubic SrVO _3 perovskite oxide is an attractive candidate for high-temperature energy applications due to its favorable features such as multiple oxidation state cations, high structural and thermal stabilities, ability to accommodate a large number of oxygen vacancies, and cost-effectiveness. Herein, the temperature-dependent reduction properties of SrVO _3 have been studied using accurate first-principles calculations to reveal the effects of oxygen vacancies and temperature on the reduction potential of SrVO _3− _δ , δ = 0–0.125. The reduction potential of SrVO _3− _δ was found to be significantly impacted by increasing oxygen vacancy concentration and temperature. Analysis of the electronic and vibrational properties of SrVO _3− _δ for differing δ revealed the origin of this reduction behavior. The electronic structure analysis shows that the reduction of SrVO _3− _δ upon oxygen vacancy formation is highly localized to the neighboring V ^4+ t _2g states in the vicinity of the oxygen defect, irrespective of δ . A comparison of the vibrational density of states of defect-free and reduced SrVO _3 demonstrated that the ionic contributions to the phonon density of states, and hence to the thermal contributions to the SrVO _3− _δ lattices, were significantly altered by the introduction of oxygen vacancies, which ultimately impacted the temperature-dependent reduction behavior of SrVO _3− _δ .